Interactive Lighting to Maintain Concentration: Salman Al Farisi Bandung Full-Day School - Athifa Sri Ismiranti; Bagus Handoko (Center for Scientific Publication, 2023)
Nowadays, the times affect the development of the education system for children. Full-time employment parents and the problem of leaving their children unattended and without essential activities are reasons full-day schools are in great demand. The learning conditions for a relatively long time and the various activities implemented in this full-day school affect the need for unique facilities compared to other schools, especially in maintaining children’s concentration in learning. This research uses a literature review, field surveys, and interviews with case studies of Salman Al Farisi Elementary School, a pioneer of full-day school in Bandung with an integrated Islamic education concept. Lighting is an interior architecture element that mainly affects student concentration in the classroom. Due to the existing problems, an interactive lighting system must be implemented in Salman Al Farisi Elementary School classrooms to support activities and maintain student concentration in learning. Arduino devices as artificial intelligence tools have the potential to be used in Salman Al Farisi Elementary School classrooms to create an interactive lighting system. The interactive lighting system required is the adjustable room light to maintain student concentration according to the ongoing activity.